Perbandingan dalam Film Animasi The Little Mermaid (1989) dan Versi Adaptasi Live-Action The Little Mermaid (2023) - Zalfa Melanie putri (Syntax Idea)
Animated films are one of the most popular children's literature, various themes and genres of animated films are certainly like friends for children. This study aims to analyze the comparison in an animated film and its adaptation work qualitatively and comparative in the overall exposure of the animated film The Little Mermaid (1989) and The Little Mermaid (2023) live-action produced by Disney with the musical-fantasy genre, where this study focuses on the transformation (alih wahana). An animation that is made into a live-action certainly experiences differences in terms of addition, reductions and also varied changes for the needs of the film, which is the main topic in this study, that The Little Mermaid (1989) and The Little Mermaid (2023) have a quite major differences in their characters, and addition which was not include in the animations, and because of that the live-action itself have problems like pros and contras.